ANALISIS PENERAPAN K3 TERHADAP KINERJA KARYAWAN OPERATOR DUMP TRUCK PADA FRONT PENAMBANGAN PT BUKIT ASAM TBK - Dhico Falentino; Suhardiman Gumanti; Dedi Yansen (Jurnal Humaniora & Sosial Sains, 2025)
Occupational Safety and Health (OHS) impacts the performance of dump truck operators at the mining front at PT Bukit Asam Tbk, Tanjung Enim. Given the high occupational risk associated with the mining sector, attention to the OHS system is crucial for maintaining safety and improving work efficiency. The research method employed direct observation and interviews with dump truck operators and OHS supervisors at the mining site. The analysis showed that OHS elements such as the use of Personal Protective Equipment (PPE), occupational safety training, and adherence to operational procedures significantly impact employee performance. It was also found that violations of OHS standards still occur due to individual negligence and a lack of regular training frequency. Optimal OHS implementation results in a safer work environment, reduced stress levels, and improved operator performance. Recommendations from this study emphasize the importance of ongoing OHS training and more consistent oversight of occupational safety practices.